The relationship between upper extremity strength and performance in elite amputee football players - Gunaydin, G. (Baltic Journal of Health and Physical Activity, 2020)
Background: Despite having similar requirements to regular football, amputee football may also require different dynamics due to using crutches. This study investigated the relationship between upper extremity strength and performance in amputee players.